2013
DOI: 10.1002/chem.201302464
|View full text |Cite
|
Sign up to set email alerts
|

General and Selective C‐3 Alkylation of Indoles with Primary Alcohols by a Reusable Pt Nanocluster Catalyst

Abstract: The platinum rule: Heterogeneous, additive-free C-3 selective alkylation of indoles by aliphatic and aromatic alcohols proceeded under transfer hydrogenation conditions with the reusable Pt/θ-Al2 O3 catalyst (see scheme; TON=turnover number).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 30 publications
(42 reference statements)
2
41
0
1
Order By: Relevance
“…On the other hand, reacting indole 1 a with preformed imine 8 and replacing benzoquinone by hydroquinone led to full conversion and product 3 a was isolated in 42 % yield. These results demonstrated that benzoquinone acted as a hydrogen shuttle in the overall process, which appears to proceed by a hydrogen‐borrowing mechanism analogous to the known metal‐based protocols 6a,b. 9…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…On the other hand, reacting indole 1 a with preformed imine 8 and replacing benzoquinone by hydroquinone led to full conversion and product 3 a was isolated in 42 % yield. These results demonstrated that benzoquinone acted as a hydrogen shuttle in the overall process, which appears to proceed by a hydrogen‐borrowing mechanism analogous to the known metal‐based protocols 6a,b. 9…”
Section: Methodsmentioning
confidence: 77%
“…using Shvo’s ruthenium catalyst 6a. The analogous process using benzyl and aliphatic alcohols has also been described employing catalytic Pt nanoclusters6b and stoichiometric hydroxide base 6c. These high‐temperature reactions (140–150 °C for 24 h) are initiated by dehydrogenation of the amine or alcohol to give an imine or aldehyde electrophile 5 , followed by nucleophilic addition–elimination of indoles 1 furnishing a putative 1‐azadiene intermediate 6 .…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the base, LiOtBu, KOtBu, and Cs 2 CO 3 were found to be equally effective for this transformation (see Table S1, Supporting Information). A decrease in temperature or the amount of base led to unreacted indole, with inferior yield of the desired product (entries [12][13][14]. Omission of the catalyst or base resulted in no desired product formation (entries 15-16).…”
Section: Iridium-catalyzed Methylation Of Indoles and Pyrroles Using mentioning
confidence: 99%
“…(27)]. Hier ist keine Base notwendig, weil θ‐Al 2 O 3 die Aldolkondensation des Indols mit dem in situ erzeugten Aldehydintermediat erleichtert.…”
Section: Heterogene üBergangsmetallkatalysierte C‐alkylierung Von Keunclassified